The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s10936-012-9234-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuter is not Common in Dutch: Eye Movements Reveal Asymmetrical Gender Processing

Abstract: Native speakers of languages with transparent gender systems can use gender cues to anticipate upcoming words. To examine whether this also holds true for a non-transparent two-way gender system, i.e. Dutch, eye movements were monitored as participants followed spoken instructions to click on one of four displayed items on a screen (e.g., Klik op [Formula: see text] rode appel [Formula: see text], 'Click on the[Formula: see text] red apple[Formula: see text]'). The items contained the target, a colour- and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 28 publications
6
22
0
Order By: Relevance
“…The same effect has since been found for article-noun combinations whose onsets did not overlap (Paris et al 2006 for German; Lew-Williams and Fernald 2007 for Spanish, Loerts et al 2013 for Dutch and Hopp 2013 for German). Lew-Williams and Fernald (2007) showed that the gender anticipation effect can even be found in preschoolers.…”
Section: Eye-tracking and Grammatical Processingsupporting
confidence: 56%
See 1 more Smart Citation
“…The same effect has since been found for article-noun combinations whose onsets did not overlap (Paris et al 2006 for German; Lew-Williams and Fernald 2007 for Spanish, Loerts et al 2013 for Dutch and Hopp 2013 for German). Lew-Williams and Fernald (2007) showed that the gender anticipation effect can even be found in preschoolers.…”
Section: Eye-tracking and Grammatical Processingsupporting
confidence: 56%
“…Hopp (2013) investigated native English learners of German, which has a nontransparent gender system (see Chapter 1), and found anticipatory effects, suggesting that native-like performance on gender can be found without a gender system being present in the L1 and in the absence of phonological or form regularities of gender agreement, like those characteristic of Spanish. Loerts et al (2013) investigated gender processing in Slavic learners of Dutch, a language which is also non-transparent. Their findings, like those of , suggest that a different expression of gender in the L1 might modulate the degree to which gender marking can be used in L2 processing, since Polish learners of Dutch, who encode gender in the L1 but not on articles, showed no effect of gender facilitation.…”
Section: Eye-tracking and Grammatical Processingmentioning
confidence: 99%
“…Furthermore, morpho-syntactic properties of the language also determine whether an anticipation effect is found. Loerts et al (2013) found anticipation effects for the masculine gender in Dutch, but not for the neuter, and related this finding to the fact that the neuter gender is used to form all diminutives in Dutch, regardless of lexically specified gender. Since all nouns can in principle occur with a diminutive suffix, the neuter gender does not facilitate anticipation of upcoming nouns.…”
Section: Introductionmentioning
confidence: 86%
“…The participant's eye movements reflect whether the presence of gender markers facilitates looks to objects that match the grammatical gender of the article, i. e., if the participant uses the gender information to predict the target noun. Although predictive effects triggered by gender information on articles and adjectives have been observed in many languages, e. g., French (Dahan et al 2000), Spanish (Grüter et al 2012;LewWilliams and Fernald 2007), Russian (Sekerina and Trueswell 2011), German (Hopp 2016), and Dutch (Loerts et al 2013), this effect can be modulated by the population tested, the morpho-syntactic system of the language, and the experimental set-up. Children and older adults, speakers with low working memory capacity, and L2 learners show smaller or no signs of anticipation of upcoming language compared to monolingual young controls (Huettig and Mani 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This study investigated if second language (L2) learners can come to use determiners predictively in their L2. In grammar‐based prediction, determiners have been among the most frequently investigated predictive cues, and determiner‐based prediction has been found in several languages, such as Spanish (e.g., Dussias, Valdés Kroff, Guzzardo Tamargo, & Gerfen, ; Lew‐Williams & Fernald, ), French (e.g., Dahan et al., ; Foucart & Frenck‐Mestre, ), and Dutch (e.g., Loerts, Wieling, & Schmid, ; Sabourin & Stowe, ).…”
Section: Introductionmentioning
confidence: 99%